Functional state dynamics in cross-country skiers in the summer and autumn preparatory phase - Garnov, I. O.; Loginova, T. P.; Varlamova, N. P.; Potolitsyna, N. N.; Chernykh, A. C.; Bojko, E. R. (Pedagogy of Physical Culture and Sports, 2021)
Background and Study Aim. To study changes in the functional state of professional Russian cross country skiers in the course of the preparatory phase and their effects on their competition ratings. Materials and methods. In this study we examined 10 cross-country skiers. The functional state was assessed through a maximal load bicycle ergometer test, coordination and special performance tests. Concentrations of lactate and cortisol were checked in the blood plasma of participants. Results. The training effects on general physical preparedness and special physical preparation in September in comparison with June were observed as an increased number of pull-ups on a pull-up bar (by 14%) and decreased time of the roller ski test (by 4%). In autumn higher systolic (by 11%) and diastolic (by 10%) arterial blood pressure levels, higher levels of plasma lactate and cortisol (by 48% and 64%, respectively) were detected (p<0.05). At anaerobic threshold the following increased: total performance capacity (by 13%), oxygen consumption (by 14%), watt pulse (by 5%), respiratory minute volume, oxygen utilization coefficient, and oxygen pulse (by 15%) (p<0.05-0.01) at rest before the ergometer test. In September upon completion of the ergometer test we observed an increase of oxygen pulse (by 7%), watt pulse (by 10%), and oxygen utilization coefficient (by 24%) (p<0.05). In autumn at the 5th minute of recovery after the ergometer test the heart rate recovered 11% faster, blood lactate - 29% faster, and the oxygen utilization rate increased by 15% (p<0.05-0.01). In June no statistically significant correlations were found between the studied indicators. In autumn statistically significant correlations appeared between indicators of the cardiorespiratory system, physical performance, and coordination test time. Conclusions. The package program for the summer-autumn training period contributes to the improvement of the functional status of the cross-country skiers and to the development of physical power, endurance, increased strength of the upper limbs, increased speed of movement on roller skis, faster and more complete recovery of physiological and biochemical parameters.